Dialektika Hukum Trading Saham Syariah di Bursa Efek Indonesia - Hana, Kharis Fadlullah (TAWAZUN: Journal of Sharia Economic Law, 2018)
This study aims to find out how the legal basis and stock trading transactions that occur in the Islamic capital market in Indonesia. This study uses a field research method that discusses legal issues regarding stock trading based on field studies from various relevant sources. The capital market is a place for corporate activities to seek additional funds to finance its business activities. In Indonesia alone there are two capital markets, namely the regular capital market and the Islamic capital market. The Islamic capital market is a new breakthrough that has been carried out as a solution to the current trend of halal investment. It also becomes very interesting for the community, especially for Muslim communities to invest their capital in the company to get results and can participate in developing the company, but the reality that happens in the market is that many companies that have been listed on the stock exchange are still operating in accordance with sharia principles . The Islamic capital market can simply be interpreted as a capital market that implements sharia principles in economic transaction activities and apart from things that are prohibited such as usury, gambling and speculation.